Determinants of non-performing consumer loans for Turkey: ARDL bounds testing approach - Yilmaz Küçük, Şeyma (Business, Management and Economics Engineering, 2022)
Purpose – the aim of this study is to specify the factors affecting the non-performing consumer loans in deposit banks operating in Turkey. Besides the internal factors specific to banks, the effect of macroeconomic factors is also investigated. Research methodology – monthly data of deposit banks operating in Turkey and data on macroeconomic indicators for the period 2005:1–2021:12 is used is the study. With these data, ARDL bound testing approach is applied. If there is cointegration relation between variables, the long and short run coefficients are estimated. Findings – with the two different models created in the study, it has been specified that macroeconomic variables and internal variables have a cointegration relationship with non-performing loans. The rise in loan interest rates and unemployment rate increase the rate of non-performing consumer loans. Conversely, the increase in deposit interest rates and the dollar exchange rate decreases the rate of non-performing consumer loans. For internal factors, it is determined that the increase in the capital adequacy standard ratio and the return on assets decreases the ratio of non-performing consumer loans. Research limitations – the major limitation of this study is to research only the factors affecting the non-performing consumer loans ratio for Turkey. Practical implications – the results obtained in the study are valuable for bank managers and investors. Administrative decisions and investment decisions by considering the factors affecting the non-performing consumer loans ratio will increase the performance of both groups. Originality/Value – studies in the literature generally consider non-performing loans for banks as a whole. However, determining the factors affecting the non-performing loans ratio on the basis of loan types will make a significant contribution to the literature. For this reason, the factors affecting the non-performing consumer loans for the Turkish market is investigated, thus contributing to the literature.